PERBANDINGAN PERTUMBUHAN DAN HASIL BEBERAPA VARIETAS KUBIS (Brassica oleracea var. capitata L.) INTRODUKSI PADA MUSIM HUJAN DI PURBALINGGA - Zulfa Mirza Azzahra; Rostaman; Ni Wayan Anik Leana (Jurnal Ilmu-Ilmu Pertanian Indonesia, 2024)
[COMPARISON OF GROWTH AND YIELD OF SOME  INTRODUCED VARIETIES OF CABBAGE  DURING THE RAINY SEASON IN PURBALINGGA]. Cabbage (Brassica oleracea var capitata L.) is a type of vegetable plant from the Brassicaceae family that has great potential for cultivation because it has an economic value and very high nutritional contents. This research aimed to evaluate the introduced cabbage varieties that have the best growth and yield in the highlands of Purbalingga Regency. The research was carried out in Serang Village, Karangreja District, Purbalingga Regency, in February-June 2023. The site was located at an altitude of 1,250 m above sea level. The experiment was arranged in a completely randomized block design (CRBD) with treatments consisting of six introduced cabbage varieties, namely Omphalos, Oxylus, Tropicana, Kaelo, Saint, and Dolares, as well as two comparison varieties, namely Grand 11 and Green Nova. Introduced cabbage varieties have varied growth, which was observed in the variables of plant height, number of leaves, age of crop formation, root length, fresh weight of roots, and age of harvest. The crop fresh weight yields for the introduced varieties Kaelo, Tropicana, and Oxylus were respectively 721.1, 683.3, and 650.8 g/plant, which was relatively uniform with the comparison variety Grand 11, namely 637.5 g/plant.